Selection of Quality Textile Materials as a Support for Supply Chain Management with the Weighted Product Method - Alvi Martunasia; Teri Ade Putra; Raja Ayu Mahessya (Universitas Putra Indonesia YPTK Padang, 2023)
Decision making is a matter that is very influential in the process of dealing with the selected alternative. At this time in making decisions is no longer just by human reason. Human limitations in thinking to solve a problem can now be assisted by computerization. The use of computers has developed from just processing data or presenting information, to being able to provide choices as a support for decision makers. The development of information technology has enabled decision makers to be made more quickly and accurately. The research aims to apply the weighted product method in reducing errors in the selection of quality textile materials. This research aims to facilitate the selection of quality textile materials. This research aims to be a good solution for khatialo shops in selecting quality textile materials. The weighted product (WP) method is one of the methods used to complete a decision-making system by considering the criteria and weights . Then proceed with the ranking process which will select the best alternative from a number of alternatives, in this case the alternative in question is the selection of quality textile materials based on the specified criteria. The results obtained with the highest rating value were achieved by the 4th alternative called Semi Sutra with the code TK04 alternative